Penile Sensory Changes After Plaque Incision and Grafting Surgery for Peyronie's Disease. Issue 10 (5th September 2018) - Terrier, Jean E.; Tal, Raanan; Nelson, Christian J.; Mulhall, John P.
Abstract: Introduction: Plaque incision and grafting (PIG) for Peyronie's disease (PD) is not devoid of complications such as erectile dysfunction and penile sensory changes. Aim: To define the rate and chronology of penile sensation loss after PIG surgery and to define predictors of such. Methods: The study population consisted of patients with PD-associated penile curvature who underwent PIG surgery with at least 6 months of follow-up. Demographics and PD factors were recorded. Patient had preoperative assessment of penile sensation and deformity. Postoperative follow-up occurred at 1 week, 1 month, 6 months, and 1 year after surgery. Neurovascular bundle elevation was conducted with loupe magnification. Main Outcome Measure: Penile sensation was evaluated with a biothesiometer and graded on a patient-reported visual analog scale (0–10) in which 0 defined a completely numb area and 10 defined perfect sensation. The degree of sensation loss was defined as extensive (any 1 area >5 cm), major (2–5 cm), and minor (≤2 cm). The penile sensation loss distribution was defined as focal (1 site) or diffuse (>1 site). Results: 63 patients were analyzed. Mean age was 56 ± 10 years. Mean duration of PD at the time of PIG was 15 ± 7 (12–38) months. 75% had curvature alone, and 25% had hourglass/indentation deformities. Mean primary curvature was 64˚ ± 28˚. The mean operation duration was 3.5 ± 1.8 hours. 21% had some degree of sensation loss at 1 week, 21% at 1 month, 8% at 6 months, and 3% at 12 months. Only 1 patient (1.5%) at 2 years continued to have extensive sensation loss on the glans and distal shaft with a very elevated sensitivity threshold. Using multivariable analysis, the only predictor of penile sensation loss ≥6 months was a duration of operation >4 hours (odds ratio = 2.1; 95% confidence interval = 1.2–3.0; P < .01). Clinical Implications: The study highlights the need during patient consent to discuss penile sensation loss. Patients should be informed that rates of penile sensation loss ranges from 2-30% and most patients will have complete resolution of any sensation loss within one year of follow-up. Strength and Limitations: To our knowledge no other studies have described the chronology and severity of penile sensation following PIG, our study demonstrates the utility of biothesiometry in measuring penile sensation before and after PIG. Number of patients and absence of control group represent a limitation. Conclusion: Sensation loss is not uncommon after PIG surgery. It decreases in frequency and severity with time with only rare cases occurring >12 months. Longer operations appeared to be more likely associated with sensation loss.